Understanding the Internet as a Moderation of E-Filling System Implementation to Taxpayer Compliance - Sitti Murniati; Fina Diana; Herlina Herlina; Lola Novita; Dzurriyyatil Izzah (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study empirically examines the Effect of E-Filling on Taxpayer Compliance and Understanding the Internet Moderating the Effect of E-Filling on Taxpayer Compliance. This research is a quantitative study that uses primary data from questionnaires to collect data. This study's population is Individual Taxpayers registered as E-Filling Taxpayers at KPP South Makassar, with as many as 29,372 taxpayers. The sampling technique used in this study was random sampling. The number of samples used was as many as 100 respondents obtained from the results of the sloven formula. The data in this study will be tested with several stages of testing, including descriptive statistical tests, research instrument tests consisting of (validity test, reliability test) classical assumption test consisting of (normality test, heteroskedasticity test, multicollinearity test) and testing of all hypotheses through Moderated Regression Analysis (MRA) analysis, partial test (t test) and determination coefficient test with the help of SPSS software version 25. The results of this study show that E-Filling has a positive and significant effect on Taxpayer Compliance, and Internet Understanding can moderate the influence of E-Filling on Taxpayer Compliance.